Módulo para la liquidación de nómina de comisiones al exterior en la Policía Nacional (2022)
The National Police of Colombia has at its disposal an information system to process the monthly salary of employees. However, the payroll process for personnel commissioned abroad is carried out in Excel. The objective of this project is to systematize this type of payroll, through the creation of a module that reduces processing time, minimizes user errors and generates the payroll reports required by the Entity. The Kanban methodology was used for the development of the system because it is a simple methodology, easy to implement and because it adjusts to the work group for its execution. As relevant results, the digitization of the information registration process, the generation of reports and the automatic notification of payroll to employees on commission abroad were obtained.